P156 Overuse of inhaled corticosteroids in asthma patients with concurrent exercise-induced laryngeal obstruction. (12th November 2015) - Porsbjerg, C; Sverrild, A; Walsted, E; Mirza, K
Abstract : Introduction: Exercise induced laryngeal obstruction (EILO) causes asthma-like respiratory symptoms (i.e. shortness of breath and wheezing) and EILO is therefore difficult to distinguish from asthma in the clinic, resulting in a diagnostic dilemma in symptom based asthma management. We aimed to elucidate if the symptom contribution from EILO affected treatment strategy in patients suffering from both asthma and EILO compared with patients suffering from asthma only. Methods: We included 28 consecutively referred subjects with verified asthma, of which 11 had concurrent EILO. At baseline and at a one-year follow-up, all subjects underwent a thorough work-up consisting of a detailed clinical interview including asthma medication history, ACQ and mini-AQLQ scores, and diagnostic tests including spirometry, Mannitol and Methacholine bronchoprovocation tests, and fractional exhaled nitric oxide. Further, all subjects underwent a continuous laryngoscopy during exercise (CLE) test verifying the severity or absence of any concurrent EILO. Results: Subjects who suffered from both asthma and EILO were prescribed higher doses of inhaled corticosteroids (ICS) as a result of the baseline work-up (P = 0.016) and were reduced in ICS doses at time of follow-up (P = 0.027) and reported a significant decrease in ACQ-scores at one-year follow-up (P = 0.016). In subjects with asthma only, there were no significant changes in ACQ scores at time of follow up despite of comparable asthma severities between groups at time of referral. Conclusion: EILO is a relevant differential diagnosis when managing patients with respiratory symptoms in a tertiary asthma clinic. Symptoms arising from EILO are difficult to distinguish from asthma symptoms, resulting in an ostensible overuse of ICS in patients with EILO. Further studies are needed to establish the clinical consequences and the optimal treatment strategy in this patient group.